Quantitative LC-MS/MS method for nivolumab in human serum using IgG purification and immobilized tryptic digestion. Issue 1 (3rd December 2019) - Abe, Kazuki; Shibata, Kaito; Naito, Takafumi; Karayama, Masato; Hamada, Etsuko; Maekawa, Masato; Yamada, Yasuhide; Suda, Takafumi; Kawakami, Junichi
Abstract : A simple and rapid LC-MS/MS method for quantification of nivolumab in human serum using immobilized trypsin coupled to IgG purification. Abstract : A liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) method is a novel approach for the quantification of therapeutic monoclonal antibody. However, this method has severe ionization suppression and time-consuming sample preparation. In the present study, we developed a simple and rapid LC-MS/MS method for quantifying serum nivolumab with good analytical performance using immunoglobulin G (IgG) purification and immobilized tryptic digestion. Surrogate peptide derived from nivolumab was identified by a hybrid quadrupole-Orbitrap mass spectrometer. IgG purification and immobilized tryptic digestion were completed within 25 minutes. The chromatographic separation was completed in 10 minutes with stepwise-gradient elution. Chromatographic peaks interfering with the surrogate peptide and its stable isotope-labeled peptide as an internal standard were not observed from serum digests. The dynamic range of the calibration curve was 2–200 μg mL −1 . The intra- and inter-assay accuracies and imprecisions were 92.2–104.5% and less than 10.0%, respectively. Serum nivolumab concentrations ranged from 12–112 μg mL −1 in 14 cancer patients. The measured concentrations in the LC-MS/MS method were strongly correlated with those in the ELISA method ( r = 0.92, P < 0.01). In conclusion, a simple and rapid LC-MS/MS method for quantifying serum nivolumab using immobilized tryptic digestion coupled to IgG purification was found to be acceptable for clinical settings.